Genome-resolved metagenomics reveals role of iron metabolism in drought-induced rhizosphere microbiome dynamics - Ling Xu; Zhaobin Dong; Dawn Chiniquy; Grady Pierroz; Siwen Deng; Cheng Gao; Spencer Diamond; Tuesday Simmons; Heidi M.-L. Wipf; Daniel Caddell; Nelle Varoquaux; Mary A. Madera; et al. (Nature Communications, 2021)
Advances in omics provide a tool to understand mechanisms for plant–microbial interactions under stress. Here the authors apply genome-resolved metagenomics to investigate sorghum and its microbiome responses to drought, identifying an unexpected role of iron metabolism.